2022
DOI: 10.1055/s-0041-1740226
|View full text |Cite
|
Sign up to set email alerts
|

Topical Medicine Potency of Musa paradisiaca var. sapientum (L.) kuntze as Oral Gel for Wound Healing: An In Vitro, In Vivo Study

Abstract: Objective Topical application of ambonese banana (Musa paradisiaca var. sapientum (L.) kuntze) stem sap gel (GEGPA) on the socket wound area showed an increase in the expression of platelet-derived growth factor-BB, while decrease in the expression of matrix metalloproteinase-2 and 9. The aim of this study is to achieve standard formulation of GEGPA through stability, viscosity, distribution area, and drugs release for oral gel wound healing. Materials and Methods This is an in vitro and in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Cell migration and proliferation are required for a range of physiological and pathological processes, including wound healing, 20 revascularization, cartilage regeneration, and bone regeneration. 21 22 Cell migration can be induced by biochemical and biophysical cues such as the mechanical properties of matrix, peptides, and growth factors in an immobilized and free form, respectively, which are referred to as mechanotaxis, haptotaxis, and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration and proliferation are required for a range of physiological and pathological processes, including wound healing, 20 revascularization, cartilage regeneration, and bone regeneration. 21 22 Cell migration can be induced by biochemical and biophysical cues such as the mechanical properties of matrix, peptides, and growth factors in an immobilized and free form, respectively, which are referred to as mechanotaxis, haptotaxis, and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Two processing methods were employed: oven-drying for six hours at 60 °C for the initial trial and indirect sun-drying for two to three days, which proved to be the best method after evaluation of the initial trial (Figure 1 for the extraction process). The processed stems were ground and sifted to produce a powder with a mesh size of 40 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In folk medicine, plantain is used for the treatment of conditions such as diabetes, ulcers, and slow-healing wounds due to its hypoglycemic, anti-ulcer, and analgesic properties. Phytochemical studies of plantain stem juice have shown the presence of tannins and alkaloids, which are pharmacologically active compounds that have been experimentally confirmed [38][39][40]. There is a significant correlation between the phenolic content of the plant and its anti-diabetic effects.…”
Section: Banana (Musa Paradisica L)mentioning
confidence: 99%